AB244. Down-regulated ECRG4 is associated with poor prognosis in renal cell cancer and is regulated by promoter DNA methylation - Li, Zesong (Transl Androl Urol, 2016)
BACKGROUND: ECRG4 has been proposed as a putative tumor suppressor gene in several tumors. However, the role and regulation of ECRG4 in the pathogenesis of human renal cancer remain largely unknown. METHODS: The mRNA and protein expression levels of ECRG4 were assessed by PCR and western blotting. Immunohistochemistry on additional renal tumor tissues was performed to study the ECRG4 expression and its association with clinico-pathological parameters. The methylation status of ECRG4 promoter was analysis by BGS. RESULTS: Our current study revealed that expression of ECRG4 is down-regulated in renal cell lines and renal cancer tissues. ECRG4 expression was significantly associated with histological grade of tumors (P<0.001), primary tumor stage (P=0.017) and distant metastasis (P=0.017). Low expression of ECRG4 was an independent prognostic indicator for survival of renal cancer patients. Silencing of ECRG4 expression in renal cell lines was associated with its promoter methylation. Moreover, ectopic expression of ECRG4 markedly inhibited cell proliferation and invasion in renal cancer cell lines. CONCLUSIONS: These results indicated that ECRG4 is frequently silenced by the methylation of promoter in renal cell cancers. ECRG4 may be a tumor suppressor in renal cancer and serve as a prognostic marker.